Decision Support System in Determining Call Center Staff Using VIKOR Method - Roy Frensal Baringbing; Zulfahmi Syahputra; Eko Hariyanto (Sean Institute, 2021)
Call center staff is a staff who works in providing repair services or service by telephone. This staff is in charge of explaining the solutions that will be carried out by the company in getting answers. Call center staff must have good manners and be smart. In getting good staff, companies can use a decision support system with the VIKOR method in determining and selecting these staff. Five criteria will be tested in determining the staff. The results of the VIKOR method can help companies in getting call center staff according to company expectations. The ranking results can determine the level of results from the VIKOR method test on call center staff who are used as candidates or alternatives. By applying this method, the search for call center staff will be better.